(1415) Update the transportation problem تحديث مشكلة النقل - Nakhla, Afaf Fouad (The Institute of National Planning, 2018)
The transportation problem is of particular interest because of its economic application and its computational simplicity. The transportation problem is commonly used to describe a particular type of linear programming problem, which has the following special structure